POTENSI KESESUAIAN JENIS TANAMAN PADA AREAL LAHAN PASCATAMBANG TIMAH (STUDI KASUS DI KECAMATAN SUNGAI SELAN KABUPATEN BANGKA TENGAH PROVINSI BANGKA BELITUNG) - Fanni, Apri; Satjapradja, Ombo; Setyaningsih, Luluk (Jurnal Nusa Sylva, 2022)
In addition to providing benefits, mining activities can result in physical, chemical, biological and marginal changes for plant growth. Criteria of plants used for revegetation of land mines are rapidly growing in the neighborhood marginal, allowing other types of grow on the land, producing fruits that are easily spread by birds, and producing a litter easier undergoing decomposition. This research aims to know the biodiversity and natural vegetation types of suitability identification for revegetation land post-mining tin. Observation of post-mining land was carried out to identify the physical and chemical properties of the soil and the type, density, and distribution of vegetation in the observation plots. Analysis of the suitability of vegetation types with rehabilitation land refers to the criteria in Permenhut No P.4/Menhut-II/2011 with modifications. Soil texture on former tin mining land was dominated by sand, is acidic, and has low nutrients. There were 35 types of plants found, ten species of trees and three types of shrubs among them, which have the potential to be used in revegetating post-tin mining land, namely. i.e., the Acacia mangium, Syzygium buxifolium, Syzygium racemosum Blume, Schima wallichii, Trema orientalis, Eugenia sp., Alstonia angustifolia, Ficus padana, Alstonia scholaris, Vitex pinnata L, Syzygium sp, Melastoma malabthricum dan Melastoma polyanthum.